Effects of Coarse Aggregate Size on the Compressive Strength of Concrete - Ogundipe, Olumide Moses; Olanike, Akinkurolere Olufunke; Nnochiri, Emeka Segun; Ale, Patrick Olu (Civil Engineering Journal, 2018)
This study investigates the effect of aggregate size on the compressive strength of concrete. Two nominal mixes, that is, 1:2:4 and 1:3:6 were used in the study. Concrete cubes were produced with 6, 10, 12.5, 20 and 25 mm aggregates for the two nominal mixes and they were subjected to compressive strength test after curing for 7, 21, 28 and 56 days. It was found in the study that the strength development follows the same trend for both nominal mixes. Also, the results show that the compressive strength increases with increasing aggregate size up to 12.5 mm, while the concrete produced using 20 mm had greater compressive strength than those produced using 25 mm aggregate. This established the importance of ensuring that the right aggregate size is used in the production of concrete. Therefore, it is recommended that careful attention must be paid to the sizes of aggregates used in the production of concrete for structural purposes.